2022
DOI: 10.1111/bjd.21241
|View full text |Cite
|
Sign up to set email alerts
|

Benefit and toxicity of programmed death-1 blockade vary by ethnicity in patients with advanced melanoma: an international multicentre observational study

Abstract: Conflicts of interest statements can be found in Appendix 1. Data availabilityDeidentified patient data will be made available upon reasonable request when legally and ethically possible. Ethics statementThis study was conducted in compliance with local institutional review board policies.X.B. and A.N.S. contributed equally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 59 publications
0
33
0
Order By: Relevance
“…Moreover, another report suggested that, although Cox multivariate analysis suggested that performance states (PS) and elevated LDH is an independent predictor of a favorable OS and PS in the palm and sole melanoma, the efficacy of nivolumab plus ipilimumab combined therapy is not superior to that of anti-PD1 Abs for the treatment of advanced acral melanoma [ 19 ]. Surprisingly, this tendency is observed not only in the Asian population but also in other ethnic populations, including Hispanic and African patients with melanoma [ 45 ]. In addition, the efficacy of anti-PD1 Abs as adjuvant therapy for up to approximately 1 year for stage III melanoma was significantly lower in acral melanoma than in cutaneous melanoma in a Japanese cohort (31 acral melanoma vs. 31 cutaneous melanoma patients, p = 0.026) [ 9 ].…”
Section: Significance Of the Blockade Of Pd1/pd-l1 Pathways For The T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, another report suggested that, although Cox multivariate analysis suggested that performance states (PS) and elevated LDH is an independent predictor of a favorable OS and PS in the palm and sole melanoma, the efficacy of nivolumab plus ipilimumab combined therapy is not superior to that of anti-PD1 Abs for the treatment of advanced acral melanoma [ 19 ]. Surprisingly, this tendency is observed not only in the Asian population but also in other ethnic populations, including Hispanic and African patients with melanoma [ 45 ]. In addition, the efficacy of anti-PD1 Abs as adjuvant therapy for up to approximately 1 year for stage III melanoma was significantly lower in acral melanoma than in cutaneous melanoma in a Japanese cohort (31 acral melanoma vs. 31 cutaneous melanoma patients, p = 0.026) [ 9 ].…”
Section: Significance Of the Blockade Of Pd1/pd-l1 Pathways For The T...mentioning
confidence: 99%
“…Therefore, it will be important to evaluate the differences in the effect of anti-PD1 Abs in the adjuvant setting between populations of different racial backgrounds in the future. Since the efficacy of anti-PD1 Ab monotherapy is limited in the ethnic populations including an Asian population [ 12 , 45 ], the development of anti-PD1 Ab-based combination therapy or biomarkers for the prediction of the efficacy of anti-PD1 Abs are needed in the future.…”
Section: Significance Of the Blockade Of Pd1/pd-l1 Pathways For The T...mentioning
confidence: 99%
“…In this issue of the BJD , an international group of investigators now adds ethnicity to the list. Bai et al 7 . investigated the relationship between ethnicity, melanoma subtypes and clinical outcome after PD‐1 immune checkpoint inhibition.…”
mentioning
confidence: 99%
“…5,6 In this issue of the BJD, an international group of investigators now adds ethnicity to the list. Bai et al 7 investigated the relationship between ethnicity, melanoma subtypes and clinical outcome after PD-1 immune checkpoint inhibition. The authors report data from 1135 patients with melanoma undergoing anti-PD-1 monotherapy from five independent melanoma centres in Australia, China and the USA.…”
mentioning
confidence: 99%
“…5,6 In this issue of the BJD, an international group of investigators now adds ethnicity to the list. Bai et al 7 investigated the relationship between ethnicity, melanoma subtypes and clinical outcome after PD-1 immune checkpoint inhibition. The authors report data from 1135 patients with melanoma undergoing anti-PD-1 monotherapy from five independent melanoma centres in Australia, China and the USA.…”
mentioning
confidence: 99%